DExD/H-Box Helicase 36 Signaling via Myeloid Differentiation Primary Response Gene 88 Contributes to NF-κB Activation to Type 2 Porcine Reproductive and Respiratory Syndrome Virus Infection - Jing, Huiyuan; Zhou, Yanrong; Fang, Liurong; Ding, Zhen; Wang, Dang; Ke, Wenting; Chen, Huanchun; Xiao, Shaobo (Frontiers in Immunology, 2017)
DExD/H-box helicase 36 (DHX36) is known to be an ATP-dependent RNA helicase that unwinds the Guanine-quadruplexes DNA or RNA, but emerging data suggest that it also function as pattern recognition receptor in innate immunity. Porcine reproductive and respiratory syndrome virus (PRRSV) is an Arterivirus that has been devastating the swine industry worldwide. Interstitial pneumonia is considered to be one of the most obvious clinical signs of PRRSV infection, suggesting that the inflammatory response plays an important role in PRRSV pathogenesis. However, whether DHX36 is involved in PRRSV-induced inflammatory cytokine expression remains unclear. In this study, we found that PRRSV infection increased the expression of DHX36. Knockdown of DHX36 and its adaptor MyD88 by siRNA in MARC-145 cells significantly reduced NF-κB activation and pro-inflammatory cytokine expression after PRRSV infection. Further investigation revealed that PRRSV nucleocapsid protein interacted with the N-terminal quadruplex binding domain of DHX36, which in turn augmented nucleocapsid protein-induced NF-κB activation. Taken together, our results suggest that DHX36-MyD88 has a relevant role in the recognition of PRRSV nucleocapsid protein and in the subsequent activation of pro-inflammatory NF-κB pathway.